Quantitative Structure-Activity Relationship Analysis of Xanthone Derivates as Cytotoxic Agents in Liver Cancer Cell Line HepG2 - Isnatin Miladiyah; Iqmal Tahir; Jumina Jumina; Sofia Mubarika; Mustofa Mustofa (Molekul, 2016)
The study of xanthone derivatives as cytotoxic agents in cancer is increasing. This study was conducted to explore the Quantitative Structure-Activity Relationship (QSAR) of xanthones as cytotoxic agents in HepG2 cells, to find compounds with better potency. The data set were taken from the previous study, involving 26 xanthone derivates and their cytotoxic activities in Inhibitory Concentration 50% (IC50). The parameters (descriptors) were obtained from quantum mechanics calculation using semiempirical AM1 method and QSAR models determined with principle component regression, with log (1/IC50) as a dependent variable and five latent variables as independent variables. From the 26 main descriptors, PCR reduced them to five latent variables (1st– 5th LV). The QSAR analysis gave the best model as follows: log (1/IC50) = 4.592 – 0.204 LV1 + 0.295 LV2 + 0.028 LV3 (n = 26, r = 0.571, SE = 0.234, Fcount/Ftable ratio = 1.165, PRESS value = 3.766). The study concluded that the descriptors contributed to anticancer activity were volume, mass, surface area, log P, dipole moment, HOMO energy, LUMO energy, and atomic net charge of some atoms. Modifications of substitution that would contribute to cytotoxic activity can be performed at phenyl ring A and C, but not at B.